The research on model construction and application of coal mine CPS perception and control layer. (25th June 2019) - Ren, Ping; Li, Jingzhao; Yang, Dayu
An embedded cyber-physical system (CPS) is an integration of computation with physical processes, which is the result of interaction between physical layer and information layer. In order to describe the relevant characteristics of coal mine cyber-physical system accurately, in this paper, we first analyse the parametric model of infection control layer and construct the continuous-time system model, including the non-memory continuous time system model, the memory system model, the feedback control system, and the discrete-time system model. During the actual production process, because some systems are continuous time and discrete time hybrid systems, by analysing the parameters of inclined lane signal subsystem, anti-wrong turnout subsystem, anti-slip car subsystem, frequency control system, such as system function, input signal, state transition, control output, the hybrid system state model with n inputs and m outputs is proposed, besides, the parameters application model of perception and control layer is obtained. In practical application, the architecture has achieved good results.